Estimating black soldier fly larvae biowaste conversion performance by simulation of midgut digestion. (1st July 2020) - Gold, Moritz; Egger, Julia; Scheidegger, Andreas; Zurbrügg, Christian; Bruno, Daniele; Bonelli, Marco; Tettamanti, Gianluca; Casartelli, Morena; Schmitt, Eric; Kerkaert, Ben; Smet, Jeroen De; Campenhout, Leen Van; et al.
Highlights: First study to mimic black soldier fly larva (BSFL) midgut digestion in vitro . Digestion products can indicate biowaste treatment performance. In vitro digestions can be a screening tool for treatment design. First study to determine BSFL diet intake and midgut region residence times. Biowaste protein and carbohydrates influence midgut residence time. Abstract: Black soldier fly larvae treatment is an emerging technology for the conversion of biowaste into potentially more sustainable and marketable high-value products, according to circular economy principles. Unknown or variable performance for different biowastes is currently one challenge that prohibits the global technology up-scaling. This study describes simulated midgut digestion for black soldier fly larvae to estimate biowaste conversion performance. Before simulation, the unknown biowaste residence time in the three midgut regions was determined on three diets varying in protein and non-fiber carbohydrate content. For the static in vitro model, diet residence times of 15 min, 45 min, and 90 min were used for the anterior, middle, and posterior midgut region, respectively. The model was validated by comparing the ranking of diets based on in vitro digestion products to the ranking found in in vivo feeding experiments. Four artificial diets and five biowastes were digested using the model, and diet digestibility and supernatant nutrient contents were determined. This approach was able to distinguish broadly the worst and best performing rearing diets. However, for some of the diets, the performance estimated based on in vitro results did not match with the results of the feeding experiments. Future studies should try to establish a stronger correlation by considering fly larvae nutrient requirements, hemicellulose digestion, and the diet/gut microbiota. In vitro digestion models could be a powerful tool for academia and industry to increase conversion performance of biowastes with black soldier fly larvae.